Identification of a Three-Glycolysis-Related lncRNA Signature Correlated With Prognosis and Metastasis in Clear Cell Renal Cell Carcinoma - Li, Tinghao; Tong, Hang; Zhu, Junlong; Qin, Zijia; Yin, Siwen; Sun, Yan; Liu, Xudong; He, Weiyang (Frontiers in Medicine, 2022)
Clear cell renal cell carcinoma (ccRCC) is a malignant disease and an energy metabolic disease. We aimed to identify a novel prognostic model based on glycolysis-related lncRNAs. With the use of Pearson correlation analysis between the glycolysis-related differentially expressed genes and lncRNAs from The Cancer Genome Atlas (TCGA) dataset, we identified three glycolysis-related lncRNAs and successfully constructed a prognostic model based on their expressions. The diagnostic efficacy and the clinically predictive capacity of the signature were evaluated by univariate and multivariate Cox, Kaplan–Meier survival and PCA analyses. The glycolysis-related lncRNA signature was constructed by AC009084.1, AC156455.1 and LINC00342. Patients grouped into high- or low-risk group according to risk score demonstrated significant difference in OS period. Univariate Cox analyses, multivariate Cox analyses and constructed nomogram confirmed that the risk score based on our signature was an independent prognosis predictor. The CIBERSORT algorithms demonstrated significant correlations among the three glycolysis-related lncRNAs and the tumour microenvironment components. GSEA analysis demonstrated canonic pathways that were enriched in the high-risk group. In vitro, the general overexpression of LINC00342 were detected in ccRCC cells. After silencing LINC00342, the aberrant glycolytic levels and migration abilities in 786-O cells decreased significantly, which might be explained by the suppressed Wnt/β-catenin signalling pathway and reverse EMT process. Collectively, our research identified the novel three glycolysis-related lncRNA signatures as a promising model for generating accurate prognoses for ccRCC patients. The specific biological mechanisms and variations need further verification.